STRATEGI PENCEGAHAN KRIMINALISASI GURU PADA SEKOLAH MENENGAH ATAS DI KOTA BANDUNG MELLUI PENDIDIKAN KEWARGANEGARAAN - Mukhlisin; Dadang; Muthaqin, Dwi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2025)
This study focuses on the phenomenon of teacher criminalization by students in Indonesia, particularly within the educational context of Bandung City. This issue has become a serious concern as it can disrupt the teaching and learning process and undermine the authority of educators. Civic Education (PKn) is considered to play a strategic role in preventing the criminalization of teachers in senior high schools. This research employs a qualitative approach using a phenomenological method to explore in-depth understandings of the experiences and perspectives of both teachers and students. Data collection techniques include in-depth interviews, participatory observation, and document analysis. The findings indicate that Civic Education serves as an effective medium to introduce students to the issue of teacher criminalization through the integration of relevant content into the curriculum and the use of varied, participatory, and contextual learning methods. Furthermore, the implementation of a hidden curriculum strategy in Civic Education contributes to character development, enhances critical awareness, and promotes students’ social responsibility toward teachers. Thus, Civic Education proves to be an essential instrument in reducing the potential for teacher criminalization and fostering a healthy, ethical, and respectful educational environment within schools.